Uma questão de método: origens, limites e possibilidades da etnografia para a psicologia social - SOUZA, Maurício Rodrigues de (2016)
Focusing the subject of research methods in social psychology, this article gravitates around three objectives: to define in detail some of the main characteristics of ethnography, to review the historical background of its origins as a scientifically legitimated practice and, finally, to discuss its utilization nowadays. As a result, it emphasizes not only the limits, but also the possibilities of ethnographical practice, sustaining that the experience of strangeness that traditionally characterized it still carries the dynamics and the critical potential which are necessary to maintain in movement the thought about alterity.